Vesicular Trafficking of Incoming Human Papillomavirus 16 to the Golgi Apparatus and Endoplasmic Reticulum Requires γ-Secretase Activity - Wei Zhang (American Society for Microbiology, 2014)
ABSTRACT The route taken by papillomaviruses from the cell surface to the nucleus during infection is incompletely understood. Here, we developed a novel human papillomavirus 16 (HPV16) pseudovirus in which the carboxy terminus of the minor capsid protein L2 is exposed on the exterior of the intact capsid prior to cell binding. With this pseudovirus, we used the proximity ligation assay immune detection technique to demonstrate that during entry HPV16 L2 traffics into and out of the early endosome prior to Golgi localization, and we demonstrated that L2 enters the endoplasmic reticulum during entry. The cellular membrane-associated protease, γ-secretase, is required for infection by HPV16 pseudovirus and authentic HPV16. We also showed that inhibition of γ-secretase does not interfere substantively with virus internalization, initiation of capsid disassembly, entry into the early endosome, or exit from this compartment, but γ-secretase is required for localization of L2 and viral DNA to the Golgi apparatus and the endoplasmic reticulum. These results show that incoming HPV16 traffics sequentially from the cell surface to the endosome and then to the Golgi apparatus and the endoplasmic reticulum prior to nuclear entry. IMPORTANCE The human papillomaviruses are small nonenveloped DNA viruses responsible for approximately 5% of all human cancer deaths, but little is known about the process by which these viruses transit from the cell surface to the nucleus. Here we show that incoming HPV16, the most common high-risk HPV, traffics though a series of vesicular compartments during infectious entry, including the endosome, Golgi apparatus, and endoplasmic reticulum. Furthermore, we show that γ-secretase, a cellular membrane-associated protease, is required for entry of the L2 minor capsid protein and viral DNA into the Golgi apparatus and endoplasmic reticulum. These studies reveal a new pathway of cell entry by DNA viruses and suggest that components of this pathway are candidate antiviral targets.